La aplicación del Non Bis In Idem en materia tributaria y su incidencia en la rentabilidad de las empresas comerciales de la provincia de Pacasmayo. - Namoc Cruz, Luis Alberto (2012)
The development of this research has been done under the current context of taxation, where the tax has been sanctioned twice for the same cause to commercial enterprises in the province of Pacasmayo. Regarding the Non Bis In Idem is a principle of sanctioning power of the Administrative Procedures Law, the tax authorities should take into account when penalizing companies, which companies are you harm in its liquidity and profitability, and everything is violating one of the early sanctioning authority with which the administration is violating the due process to punish offending companies. On the other hand, the relationship of the return to the application of Non Bis In Idem give tax matter, is that because of his business application may not be punished twice for the same cause, which will lead to not become illiquid and Profitability especially since we will not have to do double tax additions in our annual declaration of income tax. This research will influence significantly in the business sector in the province of Pacasmayo, as employers are not always the uncertainty that can be punished twice for the same cause thus generate profitability in business enterprises in our province with more private investment to stimulate farmer in parts of the entrepreneurs in our province.